2011
DOI: 10.4317/medoral.16.e175
|View full text |Cite
|
Sign up to set email alerts
|

vacA genotypes in oral cavity and Helicobacter pylori seropositivity among adults without dyspepsia

Abstract: Objective: The aims of this research were to determine the prevalence of Helicobacter pylori and its vacA genotypes in oral cavity in persons without dyspepsia and to establish the association between the presence of H. pylori in oral cavity and oral hygiene. The seroprevalence of anti-H. pylori antibodies and its associated factors were analyzed too. Study design: For the study, 200 adults without dyspepsia symptoms were selected. Dental plaque and saliva samples from each subject were obtained. H. pylori det… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
8
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(9 citation statements)
references
References 20 publications
1
8
0
Order By: Relevance
“…The s1m1/s1m2 genotypes, alone or together, were found simultaneously in saliva and gastric biopsy from the same patient [ 32 ]. These results and others [ 33 ] support our findings; however, as far as we know this is the first study of genotyping vacA in oral samples from Mexican children without dyspepsia symptoms. Otherwise, we found that s1m1/s1m2 genotypes alone or together were mostly detected in participants with mild or moderate gingivitis ( Table 4 ).…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…The s1m1/s1m2 genotypes, alone or together, were found simultaneously in saliva and gastric biopsy from the same patient [ 32 ]. These results and others [ 33 ] support our findings; however, as far as we know this is the first study of genotyping vacA in oral samples from Mexican children without dyspepsia symptoms. Otherwise, we found that s1m1/s1m2 genotypes alone or together were mostly detected in participants with mild or moderate gingivitis ( Table 4 ).…”
Section: Discussionsupporting
confidence: 91%
“…Recently, some studies have evaluated the prevalence of H. pylori cagA and vacA genes in saliva and dental plaque [ 31 33 ], but its frequency has not been extensively studied in Mexico.…”
Section: Introductionmentioning
confidence: 99%
“…More recently, some studies suggested that oral Hp infection is, to some extent, linked to the gastric Hp infection, and saliva and dental plaques might serve as a lasting settlement sites for Hp [7,8] . Some scholars confirmed that oral Hp and its gastric counterpart have identical or essentially identical genotype and Hp at different sites might come from the same strain or be the mutants of the same bacterial strain [4,9,10] .…”
Section: Discussionmentioning
confidence: 95%
“…Several studies showed the presence of H. pylori in saliva, dental plaques, oral cavity, and tonsillar tissue as well as in the esophagus [46–52]. These studies lend weight to an oral–oral route of spread of H. pylori infection.…”
Section: Transmissionmentioning
confidence: 90%
“…These studies lend weight to an oral–oral route of spread of H. pylori infection. The presence of H. pylori in oral cavity is more frequent in seropositive subjects [46], and several studies from Brazil have consistently showed an association between gastric H. pylori infection and the presence of this bacterium in the oral cavity [47–49]. Moreover, the bacterium identified in the samples of the different sites within a given subject among all patients in one study [48] and in up to 89% in another study [49] were of identical genotype.…”
Section: Transmissionmentioning
confidence: 99%